OP242 Patient-based Evidence: A Comparison Of The Views Of Patient And Clinical Engagement Participants And Committee Members. (December 2021) - Hems, Sharon; Taylor, Louise; Jones, Jan; Holmes, Eileen
Abstract : Introduction: The Scottish Medicines Consortium (SMC) conducts early health technology assessment (HTA) of new medicines on behalf of NHSScotland. Evidence from patients and carers on end-of-life and orphan medicines is gathered during Patient and Clinician Engagement (PACE) meetings. The output is a consensus statement describing a medicine's added value from the perspective of patients/carers and clinicians, which is used by SMC committee members in decision-making. This study compared the importance of factors in the PACE statement to PACE participants and committee members. Methods: A survey of ninety-eight PACE participants (consisting of forty-two patient group (PG) representatives and fifty-six clinicians) investigated the importance of quality of life (QoL) themes (family/carer impact, health benefits, tolerability, psychological benefit, hope, normal life, treatment choice and convenience) identified from an earlier thematic analysis of PACE statements. The findings from PG representatives and clinicians were compared, and the overall results were further compared with those from a previous survey of committee members (n = 26). Results: Among PACE participants who responded (twenty-six PG representatives and fourteen clinicians), 100 percent rated 'health benefits' and 'ability to take part in normal life' as important / very important. 'Convenience of administration' and 'treatment choice' received the lowest rating with fifteen percent and nineteen percent respectively of PG representatives versus seven percent of clinicians rating each as very important. 'Hope for the future' received the most diverse response with fifty-eight percent of PG representatives and fourteen of clinicians rating this as very important. In general, PACE participants rated importance of QoL themes higher than committee members (n = 21) but the rank order was similar. Differences between the proportion of PACE participants and committee members who rated themes important/very important was greatest for 'treatment choice' (sixty-seven percent versus twenty percent respectively) and 'hope for the future' (eighty-two percent versus fifty-three percent). Conclusions: The findings demonstrate some alignment between PACE participants' and committee members' responses, supporting the value of the PACE output in decision-making. Areas for further research are highlighted.